PENGEMBANGAN MEDIA SNAKE BOARD GAME UNTUK MENINGKATKAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV PADA MATERI BAGIAN-BAGIAN TUMBUHAN - Dinda Permatasari; Isna Rahmawati; Nela Rofisian (STKIP Subang, 2026)
This study was motivated by the low critical thinking skills of fourth-grade students at SD N 2 Planggu and the suboptimal use of interactive learning media in the classroom. The purpose of this study was to develop a snake board game learning medium that is appropriate, practical, and effective in improving students’ critical thinking skills in the IPAS subject. This study is a Research and Development (R&D) project using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 20 fourth-grade students at SD N 2 Planggu. Data collection techniques included interviews, observations, questionnaires, and tests. The research instruments used included an expert validation sheet, a student response questionnaire, and pretest and posttest questions. The data were analyzed using descriptive statistical techniques and N-Gain Score calculations. The results showed that the snake board game was deemed suitable based on validation by practitioner experts (80%), media experts (87.5%), and subject matter experts (97.1%). This medium was also deemed practical because it is easy to operate and capable of creating an active and enjoyable group learning atmosphere. Furthermore, this medium proved effective in enhancing critical thinking skills, as evidenced by the experimental class’s average posttest score of 93.00, which significantly outperformed the control class’s score of 72.40, supported by an average N-Gain of 0.8139 in the high category. Thus, the snake board game is a suitable, practical, and effective innovation for IPAS instruction for elementary school students.